Michelle Obama : A Life - Slevin, Peter (New York : Vintage Books, A Division of Penguin Random House LLC, 2016)
A comprehensive portrait of the First Lady describes her working-class upbringing on Chicago's South Side, her education at Princeton and Harvard during the racially charged 1980s, and her marriage to the future forty-fourth president
Chicago's promise -- South Side -- Destiny not yet written -- Orange and blackness -- Progress in everything and nothing -- Finding the right thing -- Assets and deficits -- A little tension with that -- Just don't screw it up -- I'm pretty convincing -- Veil of impossibility -- Nothing would have predicted -- Between politics and sanity -- Simple gifts -- I am no different from you.
Includes bibliographical references and index.
Keywords: Obama, Michelle, -- 1964-; Presidents' spouses -- United States -- Biography; African American women lawyers -- Biography; African American lawyers -- Biography